The effect of ingested sulfite on active avoidance in normal and sulfite oxidase-deficient aged rats. (12th February 2017) - Ozsoy, Ozlem; Aras, Sinem; Ozkan, Ayse; Parlak, Hande; Gemici, Burcu; Uysal, Nimet; Aslan, Mutay; Yargicoglu, Piraye; Agar, Aysel
Abstract: The aim of this study was to investigate the possible toxic effects of sulfite on neurons by measuring active avoidance learning in normal and sulfite oxidase (SOX)-deficient aged rats. Twenty-four months of age Wistar rats were divided into four groups: control (C), sulfite-treated group (S), SOX-deficient group (D) and SOX-deficient + sulfite-treated group (DS). SOX deficiency was established by feeding rats with a low molybdenum (Mo) diet and adding 200 ppm tungsten (W) to their drinking water. Sulfite in the form of sodium metabisulfite (25 mg/kg) was given by gavage for six weeks. Active avoidance responses were determined by using an automated shuttle box. Hepatic SOX activity was measured to confirm SOX deficiency. The hippocampus was used for determining the activity of cyclooxygenase (COX) and caspase-3 enzymes and the level of prostaglandin E2 (PGE2) and nitrate/nitrite. SOX-deficient rats had an approximately 10-fold decrease in hepatic SOX activity compared with normal rats. Sulfite did not induce impairment of active avoidance learning in SOX-deficient rats and in normal rats compared with their control groups. Sulfite had no effect on the activity of COX and caspase-3 in the hippocampus. Treatment with sulfite did not significantly increase the level of PGE2 and nitrate/nitrite in the hippocampus.